Kepemimpinan Pendidikan dalam Al-Qur’an - Isna Nurul Inayati (Jurnal Tarbiyatuna : Kajian Pendidikan Islam, 2017)
Problems related to moral decadence, industrialization of education and the crisis of leadership is one of the problems that must be faced by the community in the current era of globalization. To face this challenge, the institution appears to be necessary to increase the quality towards better. Efforts to improve the quality of education will not be detached from the role of educational leaders who in this case is the head of school as top figures who "manage" all educational activities. As a manager in an educational institution is already a school principal should act in accordance with the rules and the norms in force and in accordance with the teachings of Qur'an corridor, that is for the sake of the benefits of good creatures in the world and in the hereafter . On the basis of this, then this study attempt formulated description of Islamic education, especially the education leadership as organisatoris in the world of education in terms of the verses of the Qur'an.